Graphene oxide optimization synthesis for application on laboratory of Universidade Franciscana - Salles, Theodoro da Rosa; Rodrigues, Higor de Bitencourt; Bruckmann, Franciele da Silva; Alves, Lauro Cezar Santos; Mortari, Sérgio Roberto; Bohn Rhoden, Cristiano Rodrigo (Disciplinarum Scientia | Naturais e Tecnológicas, 2021)
Graphene oxide (GO) is a 2D material derived from graphene, having a hexagonal arrangement crystal structure together with the addition of various oxygenated functional groups, epoxides, alcohols, ketones, carbonyls and carboxyls. Hummers and Offeman, reported in 1958 a synthesis method that is still employed to the present day, only with few adaptations. Thus, graphite is oxidized by treatment with potassium permanganate and sodium nitrate in concentrated sulfuric acid. Recently our research group evaluated several methodologies described in the literature, about the current synthesis of GO and the respective adaptations and improvements to the Hummers method. And based on these literary accounts, we developed a synthesis mechanism that could be applied in standard laboratory conditions attending demands for further research using the GO, which demonstrated good yield with simple purification method and relatively short time to synthesis.